2000
DOI: 10.1007/pl00011721
|View full text |Cite
|
Sign up to set email alerts
|

Advanced gastric glandular-endocrine cell carcinoma with 1-year survival after gastrectomy

Abstract: Primary gastric endocrine cell carcinoma (ECC) is extremely rare. In general, when it is advanced, gastric ECC causes extensive ulceration (type 2) and invades or metastasizes to other organs, frequently to the liver and sometimes to the lungs or bones, and carries a poor prognosis. We herein report a 67-year-old man with advanced gastric ECC of extensive-polypoid shape (type 1) but without distant metastasis, who underwent total gastrectomy and treatment with oral tegafur-uracil (UFT), and showed no sign of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…5D). These results correspond to the report that early gastric ECC is usually observed as a polypoid lesion arising from deep mucosa or submucosa, while later, a crater-like ulceration develops, most likely due to its rapid proliferation [1]. For this reason, finding an early ECC (such as T1 stage) may be very difficult compared to GC.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…5D). These results correspond to the report that early gastric ECC is usually observed as a polypoid lesion arising from deep mucosa or submucosa, while later, a crater-like ulceration develops, most likely due to its rapid proliferation [1]. For this reason, finding an early ECC (such as T1 stage) may be very difficult compared to GC.…”
Section: Discussionsupporting
confidence: 55%
“…Extrapulmonary sites of ECC account for 4% of all cases [12], and, in particular, gastric ECC is extremely rare, accounting for 0.1%-0.2% of all gastric carcinomas [1][2][3][4]. We employ the term "endocrine cell carcinoma (ECC)", because the term "small" is not clearly defined in extrapulmonary lesions, and this neoplasm is believed to originate from endodermally derived stem cells [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric endocrine carcinoma (EC) is an uncommon tumor of the stomach and it has been reported that 0.1-0.6% of gastric cancers exhibit endocrine cell differentiation [1]. In general, the prognosis of patients with this tumor is extremely poor because gastric EC has aggressive biological behavior and frequently metastasizes to lymph nodes and the liver even in the early stages of the disease [2].…”
Section: Introductionmentioning
confidence: 99%
“…Since Matsusaka et al described this variant first in 1976, less than 230 cases have been reported in the literature [62]. This tumor also has been referred to "oat cell carcinoma" and "atypical carcinoid" and accounts for 0.1 -0.6% of total gastric cancers [63,64]. The mean age of presentation is 65 years (range, 42 to 84 years) and it commonly affects males [65].…”
Section: Neuroendocrine Cell Carcinomamentioning
confidence: 99%